2023
DOI: 10.3389/fimmu.2022.1041177
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chimeric antigen receptor T cell therapy and autologous stem cell transplant in relapsed or refractory diffuse large B-cell lymphoma: A systematic review

Abstract: BackgroundWe aimed to compare the efficacy of chimeric antigen receptor T (CAR-T) cell therapy with that of autologous stem cell transplantation (auto-HSCT) in relapsed/refractory diffuse large B cell lymphoma (R/R DLBCL).Research design and methodsWe searched eligible publications up to January 31st, 2022, in PubMed, Cochrane Library, Springer, and Scopus. A total of 16 publications with 3484 patients were independently evaluated and analyzed using STATA SE software.ResultsPatients who underwent CAR-T cell th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…The results of axi-cel therapy were published in the ZUMA-1 trial and comparing these results with the older SCHOLAR-1 trial demonstrated an overall survival benefit of an additional 20% at 2 years in the CAR-T arm [ 27 ]. These data strongly favor CAR-T therapy over autologous bone marrow transplantation, as was also investigated in a systematic meta-analysis showing the superiority of CAR-T [ 28 ]. However, the data presented in this paper outlines that a certain population of patients can still benefit from autologous transplantation, especially if CAR-T is not universally available.…”
Section: Discussionmentioning
confidence: 99%
“…The results of axi-cel therapy were published in the ZUMA-1 trial and comparing these results with the older SCHOLAR-1 trial demonstrated an overall survival benefit of an additional 20% at 2 years in the CAR-T arm [ 27 ]. These data strongly favor CAR-T therapy over autologous bone marrow transplantation, as was also investigated in a systematic meta-analysis showing the superiority of CAR-T [ 28 ]. However, the data presented in this paper outlines that a certain population of patients can still benefit from autologous transplantation, especially if CAR-T is not universally available.…”
Section: Discussionmentioning
confidence: 99%